Increasing Mathematical Literacy and Numeracy Abilities with Problem-Based Learning Model Through Technological Pedagogical Content Knowledge - Hutajulu, Masta; Minarti, Eva Dwi (Hexagon: Jurnal Ilmu dan Pendidikan Matematika, 2024)
The background of this research was that nowadays high school students are required to have a significant understanding and appreciation of mathematics. The fact was that students experience difficulties in learning mathematics, including their mathematical literacy and numeracy abilities. The aim of this study was to investigate the significance of the effect of the PBL learning model using TPACK on students' mathematical literacy and numeracy abilities; The method used in this research was quasi-experimental. The statistical analysis tool used was the MANOVA test which is used to analyze two dependent variables (mathematical literacy and numeracy abilities) simultaneously. Then used the t-test of two independent and dependent samples. The research sample was class XI at one of the public high schools in the city of Bandung, consisting of 2 classes. The results showed that the achievement and improvement of mathematical literacy and numeracy abilities jointly owned by students in the two learning groups showed a significant difference. The conclusions obtained in this study were: (1)there were differences in achievement and improvement in mathematical literacy and numeracy abilities simultaneously between students who received the PBL learning model using TPACK and a scientific approach; (2)there was no difference in increasing mathematical literacy abilities between students who get the PBL learning model using TPACK and scientific; (3)there was a difference in increasing mathematical numeracy abilities between students who get the PBL learning model using TPACK and scientific.